Functions of cell surface galectin-glycoprotein lattices - Rabinovich, Gabriel Adrián (2007)
Programmed remodeling of cell surface glycans by the sequential action of specific glycosyltransferases can control biological processes by generating or masking ligands for endogenous lectins. Galectins, a family of animal lectins with affinity for beta-galactosides, can form multivalent complexes with cell surface glycoconjugates and deliver a variety of intracellular signals to modulate cell activation, differentiation, and survival. Recent efforts involving genetic or biochemical manipulation of O-glycosylation and N-glycosylation pathways, as well as blockade of the synthesis of endogenous galectins, have illuminated essential roles for galectin-glycoprotein lattices in the control of biological processes including receptor turnover and endocytosis, host-pathogen interactions, and immune cell activation and homeostasis.